Growth performance, linear body measurements and carcass characteristics of intact and castrated growing pigs - NJOKU, C P; AINA, A B J; SOGUNLE, O M; ODUGUWA, O O (The Indian Journal of Animal Sciences, 2013)
A study was conducted to determine the growth performance, linear body measurements and carcass characteristics of intact and castrated growing pigs. A total of forty-eight Large White male pigs of eight weeks old with initial average weight of 7.16Â±0.45 were randomly assigned to two treatments with each treatment consisting of three replicates of eight pigs each. Twentyfour of the experimental animals were castrated while the remaining twenty four were left intact. Data were collected weekly and carcass evaluation was carried out at the end of the experiment. The experiment was arranged in a Completely Randomised Design. Castrated boars recorded better values for final body weight (68.46 kg) and daily feed intake (1.70 kg) when compared to 60.04 kg and 1.37 kg, respectively for the intact boar. The intact boar had better values on feed conversion ratio (4.55), daily feed cost (N97.34) and cost/kg weight gain (N319.25). Height at wither and chest girth had higher values (1.14 and 1.12 cm) recorded by the castrated boar when compared to 0.87 and 0.94 cm of the intact boar. Castrated boar had higher values (73.67, 51.00, 25.50 kg) for final body weight, eviscerated weight and left carcass weight respectively compared to the values (67.00, 43.67, 21.67 kg) respectivelyobtained by intact boars. Intact boar recorded better value (49.02) for fat free index when compared to 43.46 obtainedby the castrated boar. It was concluded that state of boar had effect on growth performance, linear body measurementsand carcass parameters of growing pigs.